(untitled) (Eurasian Research Bulletin, 2022)
This article presents overview of the Internet’s societal significance; education is one in every of the institutions most deserving of disruption and with the best opportunities to come back of it. The article will describe about overview about internet-based education that the dominant mode of education around the world. Some general information about the internet and the role of internet technologies in science and education